Implementasi Koordinasi dalam Penyelenggaraan Otonomi Daerah - Nadeak, Hasoloan (Jurnal Bina Praja, 2009)
Coordination as one of the management functions in the implementation of regional autonomy based on Law No. 32 of 2004 concerning Regional Government, in reality has not functioned effectively and efficiently. Although coordination has also been regulated as mandated by Article 222 of Law No. 32 of 2004, it turns out that there is still a lack of coordination, especially between sectoral agencies in the regions. So that it is detrimental to the goal of regional autonomy to improve the welfare of the community. The lack of effective coordination in the implementation of regional autonomy, in addition to the failure to immediately issue various implementing regulations of the Law, is also due to the still high sectoral ego with its subjective interests, thus trivializing the function of coordination. For this reason, it is suggested that a more in-depth study is needed regarding the various problems surrounding coordination and the need for a Law that regulates coordination which also regulates sanctions for agency officials who ignore coordination.